Metal atom-doped Co₃O₄ hierarchical nanoplates for electrocatalytic oxygen evolution - Zhang, Song Lin (2022)
Electrocatalysts based on hierarchically structured and heteroatom-doped non-noble metal oxide materials are of great importance for efficient and low-cost electrochemical water splitting systems. Herein, the synthesis of a series of hierarchical hollow nanoplates (NPs) composed of ultrathin Co3 O4 nanosheets doped with 13 different metal atoms is reported. The synthesis involves a cooperative etching-coordination-reorganization approach starting from zeolitic imidazolate framework-67 (ZIF-67) NPs. First, metal atom decorated ZIF-67 NPs with unique cross-channels are formed through a Lewis acid etching and metal species coordination process. Afterward, the composite NPs are converted to hollow Co3 O4 hierarchical NPs composed of ultrathin nanosheets through a solvothermal reaction, during which the guest metal species is doped into the octahedral sites of Co3 O4 . Density functional theory calculations suggest that doping of small amount of Fe atoms near the surface of Co3 O4 can greatly enhance the electrocatalytic activity toward the oxygen evolution reaction (OER). Benefiting from the structural and compositional advantages, the obtained Fe-doped Co3 O4 hierarchical NPs manifest superior electrocatalytic performance for OER with an overpotential of 262 mV at 10 mA cm-2 , a Tafel slope of 43 mV dec-1 , and excellent stability even at a high current density of 100 mA cm-2 for 50 h.